Interatividade na paginação para dispositivos móveis: Comparação entre os sistemas Aquafadas, Adobe Dps e Mag+ - Sebrosa, Rui (2015)
Some relevant changes have altered the way how communication is spread. Mobile devices, which have seduced the average community due to their portability and interactivity, joint the already known means, thus creating a new way of communication and consequently a new way of issuing. It is indispensable that a publisher knows how long an issue takes to be elaborated in view of the most recent digital means, namely mobile phones and tablets. This quantification is no doubt of the most importance to the way how the companies considering this possibility are ruled. The present study compared the use of interactivity in the lay out of mobile devices in three different systems: Aquafadas, Adobe Dps and Mag+. Eight features integrating the three systems were studied, considering only the time that the use of interactivity has taken. The results point out differences and analogies within the three systems, still showing that the preference for one or other depends on what the work to be done demands. Aquafadas has not shown any advantage in any of the tested features. Mag+ revealed good results in five of the eight features, showing however a significant lower performance in the remaining ones. Dps revealed good results in seven of the eight tested features.